(untitled) (Journal of the College of Basic Education, 2022)
Al-Jahiz’s dialogue in his scientific career: - I am Abu Othman, Amr bin Bahr. I was (one year older than Abu Nawas. I was born in the first year of Fifty and one hundred children in the last of them) (1). - If you allow us to interrupt and joke with you, we will tell you that your words are inaccurate, despite Of what is known about you for the vastness of knowledge of speech, the abundance of exploration in it, and the severity of its limits, (2) Because you died - your womb God - in the year two hundred and fifty-five, and it exceeded ninety (3). That is, you did not reach a hundred, even if We relied on your previous determination of the year of your birth, because it was five years later, in addition to a few years